1997
DOI: 10.1182/blood.v90.7.2772
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neutrophil Apoptosis by Tumor Necrosis Factor-α: Requirement for TNFR55 and TNFR75 for Induction of Apoptosis In Vitro

Abstract: Granulocyte apoptosis is an important mechanism underlying the removal of redundant neutrophils from an inflammatory focus. The ability of many proinflammatory agents to impede this event suggests that such agents act not only in a priming or secretagogue capacity but also increase neutrophil longevity by delaying apoptosis. We have examined whether this hypothesis holds true for all neutrophil priming agents, in particular tumor necrosis factor-α (TNF-α), which has been variably reported to either induce, del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
0
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(70 citation statements)
references
References 55 publications
7
59
0
4
Order By: Relevance
“…Separate studies have reported that TNF-a and IL-6 induce or inhibit PMN apoptosis depending on the cytokine concentration or activation state of the PMNs (44,45). Additionally, Murray and colleagues demonstrated the importance of timing in TNF-a-induced PMN apoptosis (46). When apoptosis was evaluated at time points before 8 hours, TNF-a promoted PMN apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Separate studies have reported that TNF-a and IL-6 induce or inhibit PMN apoptosis depending on the cytokine concentration or activation state of the PMNs (44,45). Additionally, Murray and colleagues demonstrated the importance of timing in TNF-a-induced PMN apoptosis (46). When apoptosis was evaluated at time points before 8 hours, TNF-a promoted PMN apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a and IL-1) can alter the rate of the neutophil apoptosis in vitro [13±15]. Although the involvement of PAF in these apoptotic reactions has been suggested [16], its precise contribution remained controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of TNF-a on neutrophil apoptosis may be influenced by activation of NF-kB [41], suggesting that preparation, handling and presence of contaminating cells may be important. Recently, TNF-a was shown to have a pro-apoptotic effect on a subpopulation of neutrophils when cells are cultured for 2±8 h in vitro [30]. This effect appears critically dependent on TNF-a interaction with both TNFR55 and TNFR75.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests either that TNF-a has a minor role in determining the rate of apoptosis in neutrophils within our culture system, or that they are refractory to TNF-a , which may indicate requirements for additional regulatory signals. Timing of TNF-a addition and activation of neutrophils during enrichment procedures may greatly influence pro-and anti-apoptotic effects of TNF-a in vitro [30]. TNF-a production was undetectable in 20 h neutrophil culture supernatants by ELISA (except in cultures where rTNF-a was added, when TNF-a remained at saturating levels (.…”
Section: Synergistic Pge 2 and Cc-3052-induced Reduction In Neutrophimentioning
confidence: 99%